Does Regulation Discourage Investors? Sales Price Effects of Rent Controls in Germany - Lars Vandrei (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
We analyze the extent to which sales prices for residential housing react to rent-price regulation. To this end, we exploit changes in apartment prices across the regulation treatment threshold. We examine a quasi-natural design in the German federal state of Brandenburg using transaction price data provided by the committee of evaluation experts. Brandenburg introduced both a capping limit for existing rental contracts as well as a price ceiling for new contracts for municipalities with tight housing markets in 2014. Whether or not a municipality falls under this classification is based upon a municipality's housing market characteristics, which are translated into a specific score. This allows us to employ a regression discontinuity design with a sharp cutoff point. We compare sales prices in municipalities that are located marginally above the assignment threshold with the prices in those slightly below. Our results suggest that the regulations reduced sales prices for affected apartments by 20–30 %.
Keywords: D04; R31; R52; 330; Housing rent controls; sales prices